Q: 2x plus 6 equals -6 5x plus 7y equals 1?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

2x + 4y - 5x + 3y = 7y - 3x

1 + 7y = 5x - 2 7y = 5x - 3 - 5x = - 7y - 3 x = 7/5y + 3/5 ---------------------

(-4, -1)

The simplified expression is 3x - 7y.

Related questions

Combine like terms: -2x - 4y + 5x - 7y = 3x - 11y -2x + 5x = 3x -4y + -7y = -11y

2x + 3y = 17 3x + 4y = 24 (2x + 3x) + (3y + 4y) = (17 + 24) 5x + 7y = 41

2x + 4y - 5x + 3y = 7y - 3x

3x + 7y

1 + 7y = 5x - 2 7y = 5x - 3 - 5x = - 7y - 3 x = 7/5y + 3/5 ---------------------

(-4, -1)

-5x+7y-6z

6x plus 4y

Yes, they are. If you solve 2x + 7y = 6 for y, you get y = (-2x + 6) / 7. If you solve 7y + 2x + 6 = 0 for y, you get y = (-2x - 6) / 7. As you can see, both equations have the same slope. Therefore they are parallel. You can punch those equations into a graphing calculator and visually verify that they are indeed parallel.

2x-7y=14 2x-14=7y from this equation the slope is 2/7

The simplified expression is 3x - 7y.

5y explanaition 5x-5x=0, 0-2y=-2y, -2y+7y=5y